A novel method for the performance evaluation of institutionalized collaborative innovation using an improved G1-CRITIC comprehensive evaluation model - Feng Ye; Jun Sun; Yuyun Wang; Nadia Nedjah; Wei Bu (Journal of Innovation & Knowledge (JIK), 2023)
Innovation is directly related to development and competitiveness, and collaborative innovation in universities is an important way to give full play to the advantages of knowledge accumulation. However, because there are multiple party participants, many categories and quantities of data indicators and high dimensions of evaluation and comparison and because the process of acquiring knowledge is constantly evolving, the construction of an evaluation method and the corresponding system is a key challenge. Therefore, a performance evaluation method based on an improved order relation analysis (G1)-Criteria Important Through Intercriteria Correlation (CRITIC) and the Technique for Order of Preference by Similarity to the Ideal Solution (TOPSIS) method for collaborative innovation is proposed and discussed. Then, we design and implement a performance evaluation system for university collaborative innovation. Using data from 73 collaborative innovation centers in Jiangsu from 2015 to 2019, a basic data set is constructed to conduct an empirical analysis of performance evaluation. Furthermore, the evaluation results are compared with those of existing comprehensive evaluation methods. The experimental results show that the proposed evaluation method can objectively and effectively evaluate the performance of collaborative innovation centers. In terms of knowledge, this study draws the following key conclusions. The overall level of construction of collaborative innovation centers in Jiangsu Province is relatively high, but the overall development is unbalanced, and the level of performance of different types of collaborative innovation centers is significantly different.
Keywords: 650; Collaborative innovation; CRITIC; Improved G1; Performance evaluation; TOPSIS